IMPLEMENTASI CHARACTER EDUCATION DENGAN MODEL PROGRAM ASRAMA BAGI MAHASISWA DI AKADEMI KEBIDANAN ALIFA PRINGSEWU LAMPUNG - Basit, Abdul (STIT Pringsewu, 2019)
This study aims to determine the implementation of character education with a dormitory program model for students at the Alifa Pringsewu Midwifery Academy in Lampung. This type of research is qualitative research with descriptive analytical approach and data collection using observation, interview and documentation methodsThe results of this study are in the dormitory of the Alifa Pringsewu Midwifery Academy in Lampung, there are several character education programs, namely spiritual programs, personality development programs and character education programs that are integrated with the academic curriculum. The implementation of character education is by way of students being obliged to students to participate in activities from the spiritual program, personality development programs and taking courses in Islamic religious education in each semester and courses in Character Building. The implementation of character education has an impact on changes in attitudes / personality / morality of students both in campus life and life after graduation